2023
DOI: 10.1620/tjem.2022.j094
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Alleviated Cerebral Ischemia Reperfusion Injury in Obese Rats

Abstract: This study aimed to investigate whether fecal microbiota transplantation (FMT) provides protection for stroke injury in obese patients. Rats were fed high-fat diet (HFD) for 4 weeks and subjected to middle cerebral artery occlusion (MCAO). After FMT for 30 days, body weight, serum total cholesterol (TC) and triglyceride (TG) levels, neurological score, brain water content, and cerebral infarction volume were measured. Brain reactive oxygen species (ROS), superoxide dismutase (SOD) and malondialdehyde (MDA) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Fecal microbiota transplantation is the most efficient intervention to reconstruct the gut microbiota and might be an effective therapeutic strategy for IS. A study found that FMT attenuated cerebral ischemic injury and improved neurological deficit in obese rats, which was probably mediated by the lowering of oxidative stress and apoptosis in the brain (Xie T. et al, 2022). FMT also ameliorated and/or protected transient MCAO mice from transient cerebral ischemic injury (Benakis et al, 2016).…”
Section: Fecal Microbiota Transplantation (Fmt) In Ismentioning
confidence: 99%
“…Fecal microbiota transplantation is the most efficient intervention to reconstruct the gut microbiota and might be an effective therapeutic strategy for IS. A study found that FMT attenuated cerebral ischemic injury and improved neurological deficit in obese rats, which was probably mediated by the lowering of oxidative stress and apoptosis in the brain (Xie T. et al, 2022). FMT also ameliorated and/or protected transient MCAO mice from transient cerebral ischemic injury (Benakis et al, 2016).…”
Section: Fecal Microbiota Transplantation (Fmt) In Ismentioning
confidence: 99%
“…In a separate study, FMT was associated with the reversal of GD and stroke outcomes with neuroprotective action ( 64 ). FMT in middle cerebral artery occlusion (MCAO) animal models fed a Western-style high-fat diet was found to inhibit apoptosis by lowering the level of Bax (Bcl-2-associated X protein) and cleaved caspase-3 and increasing Bcl-2, thereby attenuating the cerebral ischemic injury possibly via reduction in oxidative stress and brain apoptosis ( 133 ). In MCAO aged mice, FMT by gavaging stool from young mice was shown to improve post-stroke recovery and survival, while the converse was observed when FMT was administered from aged mice.…”
Section: Evidence On the Benefits Of Fmt In Neurological Disordersmentioning
confidence: 99%
“…Type 2 diabetes (T2D), one of the complications of IS, may aggravate brain injury after IS (Luitse et al, 2012). In a study by Xie et al (2022) they demonstrated that FMT attenuated cerebral ischemic injury in obese IS rats and the beneficial effects of FMT may be mediated by the attenuation of oxidative stress and apoptosis in the brain. A study by Wang et al (2021) verified that fecal butyrate-producing bacteria and butyrate levels were significantly lower in Chinese AIS patients with combined T2D than in AIS patients without T2D, and through animal experiments, butyrate can alter the gut microbiota and ameliorate brain injury after acute IS.…”
Section: Fecal Microbiota Transplantation and Probiotic Interventionmentioning
confidence: 99%